Improved Mechanical Performances of Hastelloy C276 Composite Coatings Reinforced with SiC by Laser Cladding - Yuqing Tang; Zheng Lu; Xuan Zhang; Xihuai Wang; Shengbin Zhao; Mingdi Wang (Nanomaterials)
Composite coatings reinforced with varying mass fractions of SiC particles were successfully fabricated on 316 stainless steel substrates via laser cladding. The phase compositions, elemental distribution, microstructural characteristics, hardness, wear resistance and corrosion resistance of the composite coatings were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Vickers hardness testing, friction-wear testing and electrochemical methods. The coatings have no obvious pores, cracks or other defects. The phase compositions of the Hastelloy C276 coating includes γ-(Ni, Fe), Ni2C, M6C, M2(C, N) and M23C6. SiC addition resulted in the formation of high-hardness phases, such as Cr3Si and S5C3, with their peak intensity increasing with SiC content. The dendrites extend from the bonding zone towards the top of the coatings, and the crystal direction diffuses from the bottom to each area. Compared with the dendritic crystals formed at the bottom, the microstructure at the top is mostly equiaxed crystals and cellular crystals with smaller volume. When SiC powder particles are present around the crystals, the microstructure of the cladding layer grows acicular crystals containing Si and C. These acicular crystals tend to extend away from the residual SiC powder particles, and the grain size in this region is smaller and more densely distributed. This indicates that both melted and unmelted SiC powder particles can contribute to refining the grain structure of the cladding layer. The optimal SiC addition was determined to be 9 wt%, yielding an average microhardness of 670.1 HV0.5, which is 3.05 times that of the substrate and 1.19 times that of the 0 wt% SiC coating. The wear resistance was significantly enhanced, reflected by a friction coefficient of 0.17 (43.59% of the substrate, 68% of 0 wt%) and a wear rate of 14.32 × 10−6 mm3N−1·m−1 (27.35% of the substrate, 40.74% of 0 wt%). The self-corrosion potential measured at 315 mV, with a self-corrosion current density of 6.884 × 10⁻6 A/cm2, and the electrochemical charge-transfer resistance was approximately 25 times that of the substrate and 1.26 times that of the 0 wt%. In this work, SiC-reinforced Hastelloy-SiC composite coating was studied, which provides a new solution to improve the hardness, wear resistance and corrosion resistance of 316L stainless steel.